2011
DOI: 10.1016/j.jmb.2011.09.017
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Model of Phosphorylation-Based Activation and Potentiation of Tarantula Muscle Thick Filaments

Abstract: Myosin filaments from many muscles are activated by phosphorylation of their regulatory light chains (RLCs). To elucidate the structural mechanism of activation, we have studied RLC phosphorylation in tarantula thick filaments, whose high resolution structure is known. In the relaxed state, tarantula RLCs are ~50% non- and 50% mono-phosphorylated, while on activation mono-phosphorylation increases and some RLCs become bi-phosphorylated. Mass spectrometry shows that relaxed-state mono-phosphorylation occurs on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
128
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(141 citation statements)
references
References 54 publications
(123 reference statements)
13
128
0
Order By: Relevance
“…However achieving the near-atomic resolution IHM structure on frozen-hydrated thick filaments seems to be a difficult task on view that only~2-nm resolution has been achieved on the heads region of the 0.55-nm near-atomic resolution Lethocerus 3D map . This is probably a consequence of the intrinsic flexibility of the IHM paired heads arrangement (Yang et al 2015a) especially of the free swaying heads as explained below (Brito et al 2011;Sulbarán et al 2013). Interestingly, it has been recently reported that a lack of negative charge in S2 may explain why Lethocerus thick filaments display an IHM perpendicular to the filament axis, rather than a parallel one as seen in tarantula (Fee et al 2017).…”
Section: Solving the Ihm Near Atomic And The Hmm Atomic Structuresmentioning
confidence: 99%
See 3 more Smart Citations
“…However achieving the near-atomic resolution IHM structure on frozen-hydrated thick filaments seems to be a difficult task on view that only~2-nm resolution has been achieved on the heads region of the 0.55-nm near-atomic resolution Lethocerus 3D map . This is probably a consequence of the intrinsic flexibility of the IHM paired heads arrangement (Yang et al 2015a) especially of the free swaying heads as explained below (Brito et al 2011;Sulbarán et al 2013). Interestingly, it has been recently reported that a lack of negative charge in S2 may explain why Lethocerus thick filaments display an IHM perpendicular to the filament axis, rather than a parallel one as seen in tarantula (Fee et al 2017).…”
Section: Solving the Ihm Near Atomic And The Hmm Atomic Structuresmentioning
confidence: 99%
“…The earlier tarantula IHM 3DTP quasi-atomic model IHM structure imposes different heads environments explaining heads ordered release on activation The 3DTP model has both IHM heads asymmetrically arranged; so their RLC phosphorylatable serines, Ser35 and Ser45, were not similarly exposed to its specific kinases, protein kinase C (PKC) and myosin light chain kinase (MLCK) (Alamo et al 2008;Brito et al 2011) (Fig. 7a).…”
Section: Solving the Ihm Near Atomic And The Hmm Atomic Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Phosphorylation of the analogous serine in smooth muscle RLC (smRLC) is the primary mechanism of contractile regulation in that tissue. Phosphorylation of skRLC plays a similar role in some invertebrate skeletal muscles (23,24) and enhances contractility in mammalian skeletal muscle (25).…”
mentioning
confidence: 94%